Childcare and the division of parental leave - Anna Norén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
Despite several policies aimed at increasing fathers' participation in the caring of children, Swedish mothers still use the bulk of the paid parental leave which may have several negative consequences for the family e.g. in terms of weaker labor market attachment for the mother. Division of parental leave is likely affected by how parents value the costs associated with parental leave. I investigate whether a reduction in the care burden, or a decreased non-monetary cost, of parental leave through the availability of childcare for older siblings affects how the leave is divided. The effect of access to childcare is evaluated by utilizing the regional heterogeneity of the implementation of a childcare reform in Sweden in 2002 that gave children of parents on parental leave with a younger sibling the right to stay in childcare. Results suggest that availability of childcare for an older sibling during parental leave does not impact the division of parental leave between mothers and fathers.
Keywords: H31; J13; J16; 330; Childcare; Parental leave; Gender equality